2020
DOI: 10.1172/jci137265
|View full text |Cite
|
Sign up to set email alerts
|

Landscape of coordinated immune responses to H1N1 challenge in humans

Abstract: Authorship note: RL, CMS, and HC contributed equally to this work. Conflict of interest: MA, KK, BB, and JY are current or former employees of WCCT Global. DRM is an unpaid advisor for WCCT Global. ZBH is an employee of Primity Bio. PFG is an employee of the Parker Institute for Cancer Immunotherapy. KK and JY are employees of ARK Clinical Research. NA is an advisor for January Inc. and Vasognosis and a consultant for MaraBio, and has received research funding support from Alkahest. CMS has equity in and is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
3

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 78 publications
(80 reference statements)
3
25
0
Order By: Relevance
“…Nevertheless, we found that CD38 expression on different CD38 subsets only poorly correlated with levels of the established interferon surrogate parameter SIGLEC-1 [ 3 ], indicating that additional stimuli likely modulate the expression of CD38 in SLE. On pDC, CD38 is inducible by TLR agonists, such as influenza virus, and, when treated with anti-CD38 in vitro, the capacity of pDC to produce TNFa and IFNa is largely abrogated [ 43 ]. Other cells, such as antibody-secreting cells (plasmablasts and plasma cells), constitutively express high levels of CD38.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we found that CD38 expression on different CD38 subsets only poorly correlated with levels of the established interferon surrogate parameter SIGLEC-1 [ 3 ], indicating that additional stimuli likely modulate the expression of CD38 in SLE. On pDC, CD38 is inducible by TLR agonists, such as influenza virus, and, when treated with anti-CD38 in vitro, the capacity of pDC to produce TNFa and IFNa is largely abrogated [ 43 ]. Other cells, such as antibody-secreting cells (plasmablasts and plasma cells), constitutively express high levels of CD38.…”
Section: Discussionmentioning
confidence: 99%
“…post-translational protein modifications) are simultaneously quantified in precisely phenotyped immune cells, at baseline and in response to ex vivo stimulations. The approach has previously enabled the identification of clinically-relevant biological signatures predictive of patient outcomes in several clinical contexts, including infection, malignancies, stroke, and traumatic injury (Ganio et al, 2020; Gaudilliere et al, 2014; Good et al, 2018; Irish and Doxie, 2014; Myklebust et al, 2017; Rahil et al, 2020; Tsai et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…We found innate-like and adaptive T cells express a broad range of activation markers upon their release from the spleen; notably, the marker combination CD38 hi Bcl2 lo was sufficient to identify activated cells in every lineage. Cumulatively, the activated fraction of total T cells far exceeds what has been reported for other human pathogens (49,50); this indicates that T cells are indiscriminately activated by malaria parasites. In this context, it is particularly significant that MAIT cells were activated since they do not recognise peptide antigens loaded onto MHC molecules; instead, they recognise riboflavin metabolite-derived antigens presented by APCs expressing MR1 (69).…”
Section: Discussionmentioning
confidence: 74%
“…Collectively, these results suggest that innate-like and adaptive T cells are indiscriminately recruited out of circulation and activated by P. vivax in the spleen. The breadth and scale of T cell activation considerably exceeds what has been observed in other human challenge models, including typhoidal Salmonella (49) and influenza A (50).…”
Section: Resultsmentioning
confidence: 89%